THE ASSOCIATION OF BOWEL DYSFUNCTION AND FIBROMYALGIA SYNDROME - Birkan Sonel,; Deniz Evcik, (Archives of Rheumatology, 2000)
Fibromyalgia (FS) is a rheumatological syndrome that affects 1-5% of the population. Irritable bowel syndrome (IBS) is a complex of symptoms and mostly associate with FS. This study investigated the relation of FS with IBS. Fifty (34 women,16 men) patients with primary FS according to 1990 ACR criteria and 50 (37 women,13men) healthy subjects as control group were included in the study. A detailed questionnaire about bowel dysfunction was used. Bowel dysfunction was observed in 30 FS patients whereas none in controls. Thirty-three of the FS patients had abdominal distension as compared to 11 of the controls. In FS group 19 patients had constipation and 18 had diarrhea whereas 2 (p=0.011) had constipation and 4 (p=0.03) had diarrhea in control group.Thirty-five patients reported stress-related bowel dysfunction in FS group and only 1 in healthy control(p=0.00001). There was no statistically difference in laxative use between two groups (p>0.05). As a result according to self-administered questionnaire 29 of FS group had IBS (p=0.00001). In conclusion bowel dysfunction should be carefully assessed and appropriate medical therapy should be given to IBS patients with FS.